ANALYSIS OF ENGLISH TEXTBOOK FOR FIFTH GRADE ELEMENTARY SCHOOL - Tahriidl Nur Khoiroh Azaini; Evi Karlina Ambarwati (STKIP Persada Khatulistiwa Sintang, 2023)
The purpose of this study is to evaluate the English language textbook from Ministry of Education and Culture (MOEC) for grade 5 Elementary School Level, entitled “My Next Word 5”. As an evaluation method, content-analysis was used in this study. To evaluate this book, the researchers adapt the instrument from Minister of Education and Culture Regulation Number 8 of 2016 and the book evaluation from Cunnings worth (1995); (1) Materials, (2) Language (3) Materials presenting (4) Graphic. As a result of the evaluation, it was found that the textbook is suitable for learners in materials, language i.e., there was a topic that relevant with the curriculum, the content of the book is more practical so that it can improve students’ skills, there was reflection table for student on the last page in every page. This book meets the criteria, but there are a few things that could be improved, such as the presentation of culture that is balanced with the culture of the language being studied.